Investigation on microfloral association in the roots of Macrotyloma uniflorum (Lam.) Verdc., a medicinally important tropical pulse-crop and their possible applications for crop improvement: a review - Rit, Rajarshi; Choudhury, Debapriya; Mukherjee, Chandrama; Dutta, Sikha (Plant Science Today, 2023)
Macrotyloma uniflorum (Lam.) Verdc., an economically important medicinal plant belongs to the Leguminosae family. Being Afro-Asian origin, the plant has long tradition of uses. It is primarily used for its antiurolithiatic property although it has other medicinal uses. Being Leguminosae member, this plant can form rhizobial nodules and mycorrhizal associations. The rhizobia obtained from this plant are mostly belonged to Bradyrhizobium sp. Although, Rhizobium pusence has also been reported. Microbes as biofertilizers can be used to increase yield of this plant, as well as there is great potential for utilizing the microbes derived from this plant. In this review we aim to describe the plant M. uniflorum - its taxonomic characteristics, economic uses, putative active constituents, and beneficial microflora along with their applications.